(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
In this paper we wont to analyze a particular trend of contemporary theatre in which the authors-menactors, who almost came from southern Italy, starring female characters on stage without excessive external disguise. Intense and engaging performances, where the disguise is minimal but who are able, through the power of words and gestures, to make on the scene all the tragic stories of women’s fragile, each authoractor with his own personal style. Under study will be four different authors – Saverio La Ruina, Vincenzo Pirrotta, Spiro Scimone, Gianfranco Berardi – came from Sicilia, Calabria, Puglia and his personal way to be a woman, and to understand how this happens we will proceed with a little analysis of not only their performance but also theories of sexual identity and queer studies.